Pendampingan Satuan Pendidikan Untuk Percepatan Implementasi Kurikulum Merdeka (IKM) - Ajis Sumantri; Dolly Apriansyah; Dwinki Marta Pura; Jansa Pratama; Perdian Fajar Romadon (Jurnal Dehasen Untuk Negeri, 2023)
The Merdeka Mengajar Platform is a technology platform provided to become a driving partner for teachers and principals in teaching, learning and creating. The Merdeka Mengajar Platform was built to support the implementation of the Merdeka Curriculum so that it can assist teachers in getting references, inspiration, and understanding in implementing the Merdeka Curriculum. Recently, to overcome the learning crisis due to the Covid-19 pandemic, the Minister of Education, Culture, Research and Technology (Kemendikbudristek) Nadiem Anwar Makarim launched the 15th Merdeka Learning Episode, namely the Free Curriculum and the Freedom Teaching Platform, online, Friday ( 11/2). Minister Nadiem revealed, referring to various national and international studies, the learning crisis in Indonesia has been going on for a long time and has not improved from year to year. The learning crisis is increasing due to the Covid-19 pandemic which has caused learning loss and increased learning gaps. Lecture on “Education Unit Assistance Society for Accelerating Implementation of Independent Curriculum (IKM)”. Presenters consisting of 5 people took turns explaining the Implementation of the Independent Curriculum (IKM). The Merdeka Mengajar platform has many benefits that can help improve teacher competency in terms of transferring knowledge to students. The Merdeka Mengajar Platform can be used as a tool that can help teachers work so that learning objectives can be obtained and measurable. In addition to the above, the Merdeka Mengajar Platform also assists teachers in testing student understanding through assessments so that learning outcomes can be identified. The Merdeka Mengajar platform can be run using Android